Synaptic GluN2B/CaMKII-α Signaling Induces Synapto-Nuclear Transport of ERK and Jacob - Melgarejo da Rosa, Michelle; Yuanxiang, PingAn; Brambilla, Riccardo; Kreutz, Michael R.; Karpova, Anna (Frontiers in Molecular Neuroscience, 2016)
A central pathway in synaptic plasticity couples N-Methyl-D-Aspartate-receptor (NMDAR)-signalling to the activation of extracellular signal-regulated kinases (ERKs) cascade. ERK-dependency has been demonstrated for several forms of synaptic plasticity as well as learning and memory and includes local synaptic processes but also long-distance signalling to the nucleus. It is, however, controversial how NMDAR signals are connected to ERK activation in dendritic spines and nuclear import of ERK. The synapto-nuclear messenger Jacob couples NMDAR-dependent Ca2+-signalling to CREB-mediated gene expression. Protein transport of Jacob from synapse to nucleus essentially requires activation of GluN2B-containing NMDARs. Subsequent phosphorylation and binding of ERK1/2 to and ERK-dependent phosphorylation of serine 180 in Jacob encodes synaptic but not extrasynaptic NMDAR activation. In this study we show that stimulation of synaptic NMDAR in hippocampal primary neurons and induction of long-term potentiation (LTP) in acute slices results in GluN2B-dependent activation of CaMKII-α and subsequent nuclear import of active ERK and serine 180 phosphorylated Jacob. On the contrary, no evidence was found that either GluN2A-containing NMDAR or RasGRF2 are upstream of ERK activation and nuclear import of Jacob and ERK.